Factors for COVID-19 Infection that Govern the Severity of Illness - Bidisha Ghosh; Soumyadev Sarkar; Nayim Sepay; Kaustuv Das; Sukhen Das; Sujata Ghosh Dastidar (SciMedicine Journal, 2021)
Coronaviruses have been posing a serious threat to mammals and birds and a new class of SARS-CoV is creating havoc to the world after its first incidence in Wuhan City in China in December 2019. These viruses are mainly responsible for causing serious respiratory tract infections which generally appear initially as the common cold and can be lethal just like SARS-CoV. The problems seem to vary and worsen from one person to another depending on age, gender, ethnicity, blood groups, host genetics, and associated comorbidities. Complications should also arise as this virus keeps mutating and evolving. This review points out the various underlying causes behind the severity of the illness and the mechanisms associated with it. This review will help society to understand the risks and severities associated with COVID-19. Individuals with health complexities and predispositions listed in this review are the most vulnerable in terms of severity and should take every possible measure to protect themselves from getting infected. As a consequence, this will lead to a decrease in mortality rates arising from COVID-19.